An investigation regarding the implementation of automated parking systems worldwide, especially in areas with high density - Ameskamp, Heinrich Josef (2016)
This report contains classified information about the investigation regarding the implementation of automated parking systems worldwide, especially in areas with high density. The methodology is based on a multi-method qualitative study by making use of the researcher’s observations, previous knowledge, literature review, as well as semi-structured face-to-face interviews and follow-up email conversations. The overall objective of this report is to create a general understanding of the urban mobility topic, especially the parking problems and how it will develop in the future. In order to receive a better understanding of how an automated parking system can support urban mobility, the concept and how it works will be explained based on the example of SHB Saalfeld GmbH, a pioneer in this area. Combining data and facts from literature, the knowledge of SHB Saalfeld GmbH, and the interviews, the report firstly defines the concept of urban mobility and the automated parking system compared to a conventional parking system. Based on the example of SHB Saalfeld GmbH, the pioneering concept of their robotic parking system will be explained in detail and compared to competitors’ systems. Lastly, the report will finish with several implementation possibilities and financial requirements for the investment in an automated parking system.